Estimation of genetic parameters for parasite resistance and genome-wide identification of runs of homozygosity islands in Florida Cracker sheep - Hidalgo, Jorge; Estrada-Reyes, Zaira M.; Ogunade, Ibukun M.; Pech-Cervantes, Andres A.; Terrill, Thomas; Idowu, Modoluwamu D.; Taiwo, Godstime (Frontiers in Animal Science, 2023)
In this study, we estimated genetic parameters for parasite resistance traits and the distribution of runs of homozygosity islands in Florida Cracker sheep. The dataset contained 365 animals with phenotypic records at 38 days post-infection for fecal egg count (FEC), packed cell volume (PCV), FAMACHA score (FAM), and body condition score (BCS). The pedigree file contained 695 animals born between 2016 and 2020 and included 279 individuals with genotypes. Genetic parameters were estimated using a multi-trait model with a Bayesian implementation via Gibbs sampling in the GIBBS3F90 program. Heritability was 0.33 ± 0.09 for FEC, 0.31 ± 0.10 for FAM, 0.22 ± 0.09 for PCV, and 0.19 ± 0.07 for BCS. The genetic correlation between FEC and FAM was 0.51 ± 0.21; the remaining genetic correlations had large posterior standard deviations and yielded 95% posterior intervals including zero or with values out of the parameter space because of our small dataset. Analysis of the distribution of runs of homozygosity islands revealed 113 hot spots with annotated genes related to immune response and parasite resistance traits. Our results suggest that the genetic selection for FAMACHA score can be effective in improving parasite resistance because of its ease of recording, high heritability, and favorable genetic correlation with FEC. Additionally, runs of homozygosity islands related to parasite resistance could harbor important candidate genes for controlling this trait in Florida Cracker sheep.